2020
DOI: 10.3390/cancers12040918
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Treatment and Survival of Gallbladder Cancer in the Netherlands; Identifying Gaps and Opportunities from a Nation-Wide Cohort

Abstract: Gallbladder cancer (GBC) is rare in Western populations and data about treatment and outcomes are scarce. This study aims to analyze survival and identify opportunities for improvement using population-based data from a low-incidence country. GBC patients diagnosed between 2005 and 2016 with GBC were identified from the Netherlands Cancer Registry. Patients were grouped according to time period (2005–2009/2010–2016) and disease stage. Trends in treatment and overall survival (OS) were analyzed. In total 1834 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…However, the rate of curative-intent surgery did not change during the study period, similarly as reported in a Swedish population-based study [29]. Patients' overall rate of proceeding to curativeintent surgery in our study was 19%, which is lower than the resection rate reported in West Sweden (37%), Netherlands (36%) or in Ontario (46%) [29,30,38]. Differences in curativeintent resection rates might reflect an actual difference in aggressiveness to surgical treatment but may also be explained by differences in defining curative-intent resection.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, the rate of curative-intent surgery did not change during the study period, similarly as reported in a Swedish population-based study [29]. Patients' overall rate of proceeding to curativeintent surgery in our study was 19%, which is lower than the resection rate reported in West Sweden (37%), Netherlands (36%) or in Ontario (46%) [29,30,38]. Differences in curativeintent resection rates might reflect an actual difference in aggressiveness to surgical treatment but may also be explained by differences in defining curative-intent resection.…”
Section: Discussionsupporting
confidence: 82%
“…Although most of the literature on GBC is based on single-center retrospective series, a few population-based reports are available such as from Netherlands and West Sweden [28][29][30]. These epidemiological studies have shown a change in treatment patterns during a few last decades, but the survival remains largely unchanged [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…At present, overall 5-year survival rates are up to 13 % [4,5]. This poor prognosis is due to the unfavorable anatomical position of the gallbladder and non-specific symptoms, which make it difficult to diagnose clinically [6].…”
Section: Introductionmentioning
confidence: 99%
“…This poor prognosis is due to the unfavorable anatomical position of the gallbladder and non-specific symptoms, which make it difficult to diagnose clinically [6]. Only in patients with T1b/T2 tumors undergoing radical resection, long-term survival has been reported, with a 5-year survival rate of 53 % [5]. However, in the majority of cases, GBC is found at an advanced stage, when surgery is no option anymore [7].…”
Section: Introductionmentioning
confidence: 99%
“…Management of advanced, unresectable gastrointestinal cancers with palliative chemotherapy (PC) is a common and widely accepted oncologic practice as it is associated with modest survival benefit. [1][2][3] In addition to survival gain, the key objectives of PC should also be to improve symptoms and preserve quality of life (QOL). In a shared decision-making model, data regarding the impact of PC on symptom improvement and maintenance of QOL will greatly influence patients' decision regarding PC.…”
mentioning
confidence: 99%